Linguistic Dating of the Book of Qohelet: A New Angle - Samet, Nili (Vetus Testamentum, 2021)
This paper proposes a new linguistic method for dating the Book of Qohelet. While linguistic methods employed in previous studies of Qohelet led to the conclusion that it is a post-exilic book, they could not yield a more accurate dating. The methodology proposed here identifies calques in Qohelet that reflect Aramaic phrases of uneven distribution—i.e., phrases that occur only in the Aramaic dialects of a specific period. Two Aramaic calques serve as test cases: בשל אשר and כצל אשר . Tracing the inner-Aramaic development and distribution of their Aramaic equivalents, I conclude that these phrases evolved in Aramaic in the Hellenistic period, thus excluding a Persian-period dating of the relevant calques. The paper then briefly refers to the implications of these findings for the contextualization and interpretation of the Book of Qohelet.